(untitled) (Biocenosis, 2025)
The study analyzes the impact of the Sustainable Households category of the Blue Flag Ecological Program (PBAE) on the environmental practices of participating families, supported by the local committee of the Center for Research, Technological Transfer and Education for Development (CITTED), during the 2019-2022 period. This research is based on a survey conducted with 24 participating families and in-depth interviews. The results show an improvement in knowledge about environmental practices and the implementation of sustainable actions, such as efficient electricity use, water conservation, waste separation and the reduction of fossil fuel consumption. Likewise, a high family commitment to these practices was observed, reaching approximately 88%. However, lack of time and the difficulty of preparing reports were identified as challenges in the process. Additionally, only 41.7% of the total number of registered families (158) participated continuously in the program.